Student Preventions in Dealing Earthquake Disasters - Arliza, Rika (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
This research aims to reveal the knowledge of students about disasters about : pre disaster knowledge, during disaster and post disaster. This research was conducted at Senior High School State 5 Bukittinggi, West Sumatera, Indonesia. The population of this study is all students of SMA N 5 Bukittinggi. The sample was obtained by purposive random technique. Sample number counted 50 students. The research method used is survey. The results showed that 1). disaster knowledge at pre disaster stage 29.3%, 2). Disaster knowledge at during disaster with percentage 50.4%, 3). Disaster knowledge at post disaster stage indicator 50.1%.